Effects of physicochemical parameters of water on byproduct formation during electrolysis of ballast water - Lee, Ji-Hyun; Choi, Keun-Hyung; Yang, Jun Hyuk (Frontiers in Environmental Science, 2023)
There is an increased interest in the effects of various disinfection byproducts (DBPs) generated during ballast water treatment using active substances on the marine environment. In this study, we investigated the occurrence and distribution of DBPs, secondary products generated during electrolysis, using land-based tests. DBP levels under various water conditions were compared, including the chloride and bromide ion compositions, hold time, and parameters associated with organic matter. Following electrolysis, the levels of trihalomethanes (THMs) and haloacetic acids (HAAs) increased from day 0 to day 5 under all salinities, whereas those of haloacetonitriles (HANs) decreased. THMs were the dominant DBP group, followed by HAAs and HANs. Seawater exhibited the highest DBP levels, followed by brackish and fresh water. In seawater and brackish water, brominated DBPs were dominant owing to high levels of bromide ions, while chlorinated DBP concentrations were relatively higher in fresh water. After electrolysis, the specific ultraviolet absorption (SUVA) of the treated water was > 4, indicating a high likelihood of generating carbonaceous DBPs, such as trichloromethane and HAA. These results improve our understanding of the general mechanisms by which physicochemical factors affect the formation of DBPs during electrolysis treatment of ballast water, which will be useful for addressing issues regarding the treatment and release of treated ballast water, an emerging environmental concern, into the marine environment.